Acute effects of 17β-estradiol and ATP on endothelial cells; Effects of genistein and PMA on calcium response - (:unkn) unknown (My University, 2002)
Various studies have shown that 17β-estradiol (E2), has acute effects on cardiovascular system in addition to its genomic effect. Acute administration of E2 had been shown to increase intracellular free calcium concentration (Ca+2)i in human umbilical vein endothelial cells (HUVEC). The present study investigates the signalling pathway responsible for Ca+2 response to E2. In the study, the effect of E2 on phosphoinositide turnover was investigated by use of Dowex-1 anion-exchange columns after labeling cells with myo(3H)inositol. Additionally, the effects of tyrosine phosphorylation inhibitor genistein and protein kinase C activator 4β-phorbol-12β-myristate-13-acetate (PMA) on the Ca+2 response to E2 and ATP were investigated and compared in fura-2 loaded HUVEC. The data demonstrates that E2 treatment causes 45% increase in inositol phosphate production in parallel to increases in (Ca+2)i. Genistein and PMA inhibit the Ca+2 response to E2 ∼75%, 49%, while they inhibit the response to ATP ∼62%, 73% respectively. Our data suggests the involvement of PLC in the signaling stimulated by E2 and indicate the involvement of tyrosine phosphorylation and PKC. Differences in the effect of the inhibitors on E2- and ATP-induced responses suggest that there may be differences in the upstream signaling initiated by E2 and ATP, such as different roles for tyrosine phosphorylation.
Keywords: (Ca+2)i; 17β-Estradiol; ATP; Genistein; HUVEC; Inositol phosphates; Phospholipase C; PMA; Signal transduction